Recent advances in bio-microsystem integration and Lab-on-PCB technology - Sotirios Papamatthaiou; Pavlos Menelaou; Bilal El Achab Oussallam; Despina Moschou (Microsystems & Nanoengineering)
Abstract The concept of micro-total analysis systems (µTAS) introduced in the early 1990s revolutionized the development of lab-on-a-chip (LoC) technologies by miniaturizing and automating complex laboratory processes. Despite their potential in diagnostics, drug development, and environmental monitoring, the widespread adoption of LoC systems has been hindered by challenges in scalability, integration, and cost-effective mass production. Traditional substrates like silicon, glass, and polymers struggle to meet the multifunctional requirements of practical applications. Lab-on-Printed Circuit Board (Lab-on-PCB) technology has emerged as a transformative solution, leveraging the cost-efficiency, scalability, and precision of PCB fabrication techniques. This platform facilitates the seamless integration of microfluidics, sensors, and actuators within a single device, enabling complex, multifunctional systems suitable for real-world deployment. Recent advancements have demonstrated Lab-on-PCB’s versatility across biomedical applications, such as point-of-care diagnostics, electrochemical biosensing, and molecular detection, as well as drug development and environmental monitoring. This review examines the evolution of Lab-on-PCB technology over the past eight years, focusing on its applications and impact within the research community. By analyzing recent progress in PCB-based microfluidics and biosensing, this work highlights how Lab-on-PCB systems address key technical barriers, paving the way for scalable and practical lab-on-chip solutions. The growing academic and industrial interest in Lab-on-PCB is underscored by a notable increase in publications and patents, signaling its potential for commercialization and broader adoption.